Effect of broodstock density on reproduction and juvenile culture of - Zulhisyam Abdul Kari @ Abdullah; Mohd Hafiz Jamaludin; Lee Seong Wei; Yusrina Andu; Wan Ahmad Izuddin Wan Ibrahim; Sarijan Shazani (2015)

(untitled)
In this study, the effect of the broodstock density on reproduction and juvenile culture of green buffalo leech, Hirudinea manillensis was examined with six different densities (5, 10, 15, 20, 25, and 30 ind tank-1). The number of cocoons produced was significantly different among the different densities (p = 0.00) after three months of culture. Although hatching rate was not (p = 0.354), the average number of hatchings per cocoon was also significantly different (p<0.05) with 5 ind tank-1 gave the highest number (6.61±1). The 25 ind tank-1 produced the highest mortality of parent leeches (67±13.16%). According to their length and diameter, the sizes of the cocoons were not significantly different among the treatments, with the 5 ind tank-1 having the largest cocoon of 22.19±0.92 mm and 13.25±0.07 mm, respectively. The wet weight of cocoons was significantly different at p<0.05 with the 5 ind tank-1 producing the heaviest cocoons of 1.26±0.11g compared to the 25 ind tank-1producing the lightest cocoons of 0.22±0.38 g